A Jewish life on three continents : the memoir of Menachem Mendel Frieden - Frieden, Menachem Mendel, 1878-1963 (Stanford studies in Jewish history and culture., 2013)
This memoir of Menachem Mendel Frieden, translated, edited, and annotated by his grandson, recounts the history of the author's family back several generations and covers his life from the time of his birth in 1878 until the middle of the 20th century. It tells of Frieden's early years in a Lithuanian village; of his schooling, courtship and marriage in Eastern Europe; of his migration to and exploits in America early in the twentieth century; and, finally, of his settlement in Palestine in 1921 and his involvement in the project of nation building in the Land of Israel.